High performance supercapattery with RGO/TiO2 nanocomposites anode and an activated carbon cathode / Ivy Heng - Ivy , Heng (2019)
Titanium dioxide (TiO2) nanocrystals in intermediate phase of amorphous and anatase has been successfully synthesized through a simple, low temperature peroxo sol gel approach. Tranmission electron microscopy revealed that the TiO2 nanocrystals obtained have an average diameter of 8-133 nm. The effects of calcination temperature on the morphology and phase transformation were studied by annealing the samples at 200-800 °C. TiO2 nanocrystals annealed at 200 °C with diameter of 12 nm exhibited the highest specific capacitance of 26.46 C g?1 at current density of 0.2 A g?1 in 1M KOH as the electrolyte. The high specific capacity is attributed to the intermediate phase of amorphous and anatase structure which enhanced the redox active sites of the TiO2 nanocrystals. A hybrid material of reduced graphene oxide/titanium dioxide (rGO/TiO2) was successfully synthesized by facile hydrothermal technique. A different amount of GO ratios at 5%, 10%, 20%, and 30% were loaded with TiO2. It is a well-known fact that porous structure and crystallinity of resultant rGO/TiO2 play a crucial role in synergistic effect which facilitate electron transfer movement and reduce the volume changes during a charge-discharge cycle process. Based on the results obtained, an optimum of 10 wt. % GO loading with TiO2 nanocrystals revealed that electrochemical performance achieved the highest specific capacity of 116.70 C g-1 with 0.2 A g-1 among the samples. This result inferred that high efficiency of ion diffusion was obtained with low charge transfer resistance between TiO2 nanocrystals and rGO. The supercapattery was assembled in a configuration of optimized 10% rGO/TiO2 nanocomposites as anode while activated carbon as cathode. The result obtained a superior energy density of 54.37 Wh kg-1 at power density of 420.48 W kg-1. Additionally, the specific capacity still remained at 92% for 3000 charging-discharging cycles under a current density of 1 A g-1. Hence, good life cycle stability, high specific capacity and low charge transfer resistance of rGO/TiO2 nanocomposites electrode suggested that the prepared materials was a promising anode material for supercapattery application.